LOPARITE AND 'METALOPARITE' FROM THE BURPALA ALKALINE COMPLEX, BAIKAL ALKALINE PROVINCE (RUSSIA) - Chakhmouradian A.R.; Mitchell R.H.; Pankov A.V.; Chukanov N.V. (My University, 1999)
Loparite-(Ce) is a ubiquitous accessory mineral in modally diverse albite-rich metasomatic rocks of the Burpala alkaline complex, Siberia. Compositionally, the mineral approaches the ideal formula NaREETi2O6 (REE = Ce > La > Nd > Pr > Sm), and contains minor CaTiO3 (<4.8 mol.%), SrTiO3 (<4.7 mol.%) and NaNbO3 (<6.4 mol.%). The mineral is pseudocubic [ap = 3.8815(3) Å], and produces an XRD pattern similar to that of synthetic NaCeTi2O6 [Pnma, a = 5.4517(4), b = 7.7058(9), c = 5.4333(6) Å]. The atomic coordinates and isotropic thermal parameters of synthetic NaCeTi2O6 refined from an XRD powder pattern using the Rietveld method, are given. At Burpala, loparite precipitated from an alkaline REE-rich fluid during the metasomatic alteration of earlier-formed intrusive rocks. In some parageneses, loparite was replaced by `metaloparite' during the final stages of metasomatism. `Metaloparite' has the empirical formula REETi2O6-x(OH,F)x ·nH2O, and shows minor enrichment in Ca and depletion in Sr, compared to co-existing loparite. The formation of `metaloparite' involved cation leaching, hydration and ion-exchange between loparite and a fluid. `Metaloparite' is metamict at room temperature, but some samples regain the perovskite-type structure upon heating.